(untitled) (CAHIERS MAGELLANES-NS, 2024)
The article presents the results of a field experiment conducted on the effect of bentonite clay on the growth, development and productivity of winter wheat in the dry conditions of Nurota district. In field experiments, bentonite clays were used for seed coating before planting and foliar feeding in combination with organo-mineral fertilizers.